2016
DOI: 10.7755/fb.114.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Age at maturity, skipped spawning, and fecundity of female sablefish (Anoplopoma fimbria) during the spawning season

Abstract: Abstract-Accurate maturity-at-age data are necessary for estimating spawning stock biomass and setting reference points for fishing. This study is the first on age at maturity of female sablefish (Anoplopoma fimbria) sampled in Alaska during their winter spawning period, when maturity is most easily assessed. Skipped spawning, the situation where fish that have spawned in the past do not spawn during the current season, was documented in female sablefish for the first time. Determination of age at maturity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 8 publications
0
18
1
Order By: Relevance
“…The thickness of the ovarian wall has been used in several fish taxa, including Sablefish (Rideout and Tomkiewicz 2011;Rodgveller et al 2016), to determine if a fish has previously spawned and if it is skip spawning. Each sample included a portion of the ovarian wall.…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…The thickness of the ovarian wall has been used in several fish taxa, including Sablefish (Rideout and Tomkiewicz 2011;Rodgveller et al 2016), to determine if a fish has previously spawned and if it is skip spawning. Each sample included a portion of the ovarian wall.…”
Section: Methodsmentioning
confidence: 84%
“…Each sample included a portion of the ovarian wall. Previously, Rodgveller et al (2016) found that oocyte development did not vary among locations in both ovaries. A "thin" ovarian wall is easy to discern from a "thick" ovarian wall for Sablefish: in Rodgveller et al (2016) an immature mean wall width was 35 lm (95% CI = 30-41 lm) and the mean wall width for a skip spawning fish was 318 lm (95% CI = 267-370 lm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We began our conceptual life‐history model by first identifying each life‐history stage that could potentially contribute to determining the size of each sablefish year class, beginning with female condition prior to the start of the spawning season (Table ). The energetic status of females may influence their propensity to spawn, and the quality and number of eggs produced (Rodgveller, Stark, Echave, & Hulson, ; Sogard, Berkeley, & Fisher, ). Thus, the summer and fall prior to spawning (June–December) may be important for female preconditioning.…”
Section: Methodsmentioning
confidence: 99%
“…Prey availability (H1) during the months prior to spawning (June–December) may affect female condition and in turn, egg quality, egg production or even the probability of spawning in a given year. For example, given poor prey availability, individual sablefish in Alaskan waters may skip spawning in some years (Rodgveller et al., ). We included the abundance of age‐0 hake Merluccius productus (Prey hake ) and age‐0 longspine thornyhead Sebastolobus altivelis (Prey lsp ) from their most recent stock assessments (Stephens & Taylor, ; Taylor, Grandin, Hicks, Teylor, & Cox, ) as indices of prey abundance for female sablefish.…”
Section: Methodsmentioning
confidence: 99%